Spatial distribution of the daily precipitation concentration index in the Peruvian central Andes: rio Mantaro valley - Zubieta, Ricardo (2018)
High percentages total precipitation concentration in a few very rainy days can increase the potential of erosion, instability and risks of floods, these problems are common in Peru. So it is important to know about the daily precipitation. This paper presents, an investigation of the spatial and temporal patterns of daily precipitation concentration, in central Andes of Perú, the Concentration index (CI) was evaluates measurement the varying weight of daily precipitation, the contribution of the days of greatest rainfall to the total amount. The index is applied to exponential curves such as Y = aX exp(bX), which adjust the accumulated percentages of precipitation Y contributed by the accumulated percentage of days X on which it took place, in the period 1964-2004, with which it is possible to generate concentration surfaces daily pluviometric. The highest concentrations recorded in the Mantaro river valley, may be associated with the dynamics of the winds as the stream in South America, leading into the valley from the north and south, where 25% of rainy days account for 60% or more of the total number of days with rain.